Performance of eight serum cytokine/chemokine biomarkers in discriminating between active and latent tuberculosis infection in Ghana - Mensah, Gloria Ivy; Amponsah, Jones Amo; Alahaman, Nana Boakye; Anim-Baidoo, Isaac; Tetteh, John K. A.; Addo, Kennedy Kwasi; Koram, Kwadwo Ansah (Frontiers in Immunology, 2025)
IntroductionThe existing Interferon γ release assay (IGRA) tests for TB infection, lacks utility in discriminating between active TB (ATB) and latent TB infection (LTBI). This study evaluated the potential of eight serum cytokines/chemokines in differentiating LTBI from ATB and as a surrogate marker for TB treatment response.MethodsWe quantified and compared the serum levels of pro-inflammatory cytokines (TNF-α, IFN-γ, IL-12p70, IL-17A, Granzyme B) and anti-inflammatory cytokines (IL-10, IL-6, IL-4) among LTBI, ATB, and healthy controls using the Human Magnetic Luminex™ 200 system. Serum cytokine/chemokine levels were also assessed at four timepoints before and during TB treatment.ResultsAmong ATB cases, there were twice as many males (69%) as females (30%), with infectivity spanning a wide age range. IFN-γ, IL-6, IL-10, IL-4, and IL-17A levels were higher in LTBI compared to ATB. IL-12p70 was found to be a good discriminant between ATB and LTBI (21-fold increase in ATB compared to LTBI, p < 0.05) but it did not have a good predictive potential for treatment (follow up). The predictive potential of TNF-α, IL-6, IL-10, IFN-γ, IL-4, IL-17A, Granzyme B and IL-12p70 to differentiate between ATB and LTBI using AUROC was 57%, 98 %, 91%, 100%, 100%, 97%, 66% and 100% respectively.DiscussionThese findings confirm reports from other studies in different settings that LTBI and ATB express differential cytokine profiles that can be exploited as diagnostic biomarkers. Of note, the quantitative estimation of IL-12p70 may serve as a valuable marker for monitoring disease progression and treatment success in tuberculosis.